2020
DOI: 10.1371/journal.pone.0242250
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Oga haploinsufficiency increases O-GlcNAcylation but hastens ventricular dysfunction following myocardial infarction

Abstract: Rationale The beta-O-linkage of N-acetylglucosamine (i.e., O-GlcNAc) to proteins is a pro-adaptive response to cellular insults. To this end, increased protein O-GlcNAcylation improves short-term survival of cardiomyocytes subjected to acute injury. This observation has been repeated by multiple groups and in multiple models; however, whether increased protein O-GlcNAcylation plays a beneficial role in more chronic settings remains an open question. Objective Here, we queried whether increasing levels of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…OGA transgenic hearts were resistant to pathological stress due to pressure overload, with a decrease in O -GlcNAcylation levels and a decrease in hypertrophy compared to wild-type controls ( Umapathi et al, 2021 ). These results agree with those of Sujith Dassanayaka et al, who found that the OGA-deficient mice exhibited exacerbated cardiac function at 1 week following infarction ( Dassanayaka et al, 2020 ). These findings suggest that O -GlcNAcylation represents a novel therapeutic approach for cardiomyopathy ( Umapathi et al, 2021 ).…”
Section: O -Glycosylation: Type O -Glcnacylation On Heart and Vascular Wallsupporting
confidence: 92%
“…OGA transgenic hearts were resistant to pathological stress due to pressure overload, with a decrease in O -GlcNAcylation levels and a decrease in hypertrophy compared to wild-type controls ( Umapathi et al, 2021 ). These results agree with those of Sujith Dassanayaka et al, who found that the OGA-deficient mice exhibited exacerbated cardiac function at 1 week following infarction ( Dassanayaka et al, 2020 ). These findings suggest that O -GlcNAcylation represents a novel therapeutic approach for cardiomyopathy ( Umapathi et al, 2021 ).…”
Section: O -Glycosylation: Type O -Glcnacylation On Heart and Vascular Wallsupporting
confidence: 92%
“…Cortical segments, including proximal tubules and distal tubules, have lower but significant expression levels. Advances in tissue-specific gene editing tools have been used to study the importance of O-GlcNAcylation in specific extrarenal cells [ 85 , 86 , 87 , 88 , 89 , 90 ]. Ono et al (2017) [ 91 ] accessed the importance of O-GlcNAcylation for podocytes, differentiated epithelial cells involved in selective permeability through the glomerular filtration barrier [ 92 ].…”
Section: O-glcnacylation In Renal Physiologymentioning
confidence: 99%
“…Similarly, mice with catalytically inactive OGA (D285A) show small embryo size and perinatal lethality accompanied by structural defects in embryonic kidney, liver, and brain [ 103 ]. While no major defects in the cardiovascular system were detected in OGA D285A mice, depleting OGA by 50% in adult cardiomyocytes (OGA +/− -icko) elevates cardiac O-GlcNAcylation and modestly reduces ejection fraction at baseline [ 104 ]. These data suggest that OGA has important maintenance roles in the heart and cardiomyocytes.…”
Section: Impact Of O-glcnac In Physiological Models Of Injury and Pat...mentioning
confidence: 99%
“…In addition to PO hypertrophy cardiac stress, O-GlcNAcylation has also been investigated in cardiac remodeling following myocardial infarction (MI). Failing human hearts biopsied at the time of transplantation exhibit increased O-GlcNAcylation [ 104 ]. Similarly, investigations in animal models with acute MI and heart failure found increased cardiac O-GlcNAcylation, accompanied by increased OGT and decreased OGA abundance or activities [ 46 , 121 ].…”
Section: Impact Of O-glcnac In Physiological Models Of Injury and Pat...mentioning
confidence: 99%
See 1 more Smart Citation